2017
DOI: 10.3390/en10122080
|View full text |Cite
|
Sign up to set email alerts
|

The Future of the European Electricity Grid Is Bright: Cost Minimizing Optimization Shows Solar with Storage as Dominant Technologies to Meet European Emissions Targets to 2050

Abstract: Abstract:The European roadmap for the power sector dictates an 80-95% cut of existing levels of carbon dioxide emissions is needed by the year 2050 to meet climate goals. This article describes results from a linear cost optimization investment model, ELIN, coupled with a solar technology model, Distributed Concentrating Solar Combined Heat and Power (DCS-CHP), using published investment costs for a comprehensive suite of renewable and conventional electricity generation technologies, to compare possible scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Carbon intensities for these hybrid energy systems have been found to be only slightly higher than that of PV and still lower than that of CSP [41][42][43]. However, studies on the future of these two solar energy technologies with storage find CSP to be economically preferable as it offers bigger storage capacities and greater efficiencies [44,45]. In order to push costs down through more extensive deployment further government support may be necessary to make this technology competitive.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon intensities for these hybrid energy systems have been found to be only slightly higher than that of PV and still lower than that of CSP [41][42][43]. However, studies on the future of these two solar energy technologies with storage find CSP to be economically preferable as it offers bigger storage capacities and greater efficiencies [44,45]. In order to push costs down through more extensive deployment further government support may be necessary to make this technology competitive.…”
Section: Discussionmentioning
confidence: 99%
“…Moore and Shabani [36] stated that a 10-20% ESS capacity is generally needed, depending on the specific conditions of each grid, in order for the intermittent renewable energy sources such as wind and solar PV power, to be effectively integrated into power systems. In addition, the results of analysis conducted by Norwood et al [37] indicate that solar thermal, PV, and battery ESS will play an important role in meeting Europe's targets for renewable energy supply. The results of the studies above have shown that ESS relieves the burden of the power system due to increased variable renewable energy integration by mitigating the volatility of the power generation output of renewable energy, including PV, and by providing the primary and secondary reserves for frequency regulation service [21][22][23]30,31,33,[35][36][37][38][39].…”
Section: Roles Of Ess To Integrate Pv Energymentioning
confidence: 99%
“…In addition, the results of analysis conducted by Norwood et al [37] indicate that solar thermal, PV, and battery ESS will play an important role in meeting Europe's targets for renewable energy supply. The results of the studies above have shown that ESS relieves the burden of the power system due to increased variable renewable energy integration by mitigating the volatility of the power generation output of renewable energy, including PV, and by providing the primary and secondary reserves for frequency regulation service [21][22][23]30,31,33,[35][36][37][38][39]. The studies also have verified that ESS increases the economic value of variable renewable energy by storing surplus power to participate in the energy trading market, and by bringing new investment opportunities through the substitution of a need to upgrade old distribution and substation facilities [32,34,39,40].…”
Section: Roles Of Ess To Integrate Pv Energymentioning
confidence: 99%
“…[52] Other studies have also analyzed systems with an ambitious goal of 100% of RES. [36,50,58,62,81] Moreover, as the number of studies has largely increased, several tools have been proposed to assist the generation expansion planning and RES design, such as EnergyPLAN, [22] EnergyScopeTD, [49] HOMER, [37] LEAP, [75] SILVER, [55] TIMES, [39] among others. [11] However, most of these studies focus on renewable resources while keeping the electrical grid out of their analysis.…”
mentioning
confidence: 99%